LANGUAGE POLITENESS STRATEGY IN DRAMA "HARUT AND MARUT" BY ALI AHMAD BAKATSIR - Fahma Hurrosatud Diyanah; Kamal Yusuf; Nasikul Mustofa Efendi (Journal of Arabic Literature (JaLi), 2023)
Language is the primary communication tool that people always use. In increasingly modern developments, language is often used without considering the politeness established in communication. This is what makes researchers want to research language politeness strategies in drama. This research aims to examine the application of language strategies and politeness in the drama text "Harut and Marut" by Ali Ahmad Bakatsir. The research method used is a qualitative descriptive approach with data collection through the method of reading, taking notes, and then analyzing it. The results of this research reveal various strategies and principles of language politeness applied in the drama Harut and Marut. As for the results of research on language politeness strategies, according to Brown and Levinson in the drama Harut and Marut by Ali Ahmad Bakatsir, there are 12 types of Bald-on record strategies, eight negative politeness strategies, five positive politeness strategies, and 6 Bald-off record strategies. The implications of this research include the importance of language development in society and how to speak well to create an environment that pays attention to effective language politeness. The results of this research provide practical guidance for the community in improving quality and harmonious language communication..